Politics and Conflict during the Reign of Caliph Uthman ibn Affan 644-656 - Rohmatillah, Itsna; Setiawan, Agus Mahfudin; Rifai, Idris Ahmad (El Tarikh : Journal of History, Culture and Islamic Civilization, 2023)
This study discusses Politics and Conflict in Islamic History during the reign of Usman bin Affan. Usman bin Affan's 644-656 reign is considered one of the most controversial periods in Islamic history due to the many conflicts and disagreements among political leaders at that time. The aim of this study is to understand the political background during Usman bin Affan's reign, analyze the political conflicts that occurred at that time, and evaluate the impact of these political conflicts on society at that time. This study uses historical analysis methods by examining literature and primary and secondary sources related to Islamic history during Usman bin Affan's reign 644-656 . The research findings indicate that the political conflicts during Usman bin Affan's 644-656 reign were very complex and had a broad impact on society at that time. Therefore, this research is expected to provide a deeper understanding of the political history and conflicts in Islamic history and to serve as a basis for understanding the political dynamics in the future. Additionally, the results of this study can contribute to the development of knowledge of Islamic history and serve as a reference for researchers and academics in the fields of history and Islamic politics.